Pemanfaatan Neural Network Perceptron pada Pengenalan Pola Karakter - Yudhistiro, Kukuh (LPPM STIKI MALANG, 2017)
Various methods on artificial neural network has been applied to identify patterns of characters one using Perceptron algorithm. Perceptron algorithm can be used to identify patterns of characters with various input patterns that resemble letters of the alphabet so perceptron can be trained to recognize it. Perceptron algorithm is an algorithm in a neural network that includes supervised neural network.